Problems and Prospects of the Mediation Development in the Republic of Kazakhstan - Dyachuk, M. I.; Abikanov, Y. Z.; Kaliakperova, E. N. (Opción, 2019)
The aim of the study is to investigate problems and prospects of the mediation development in the republic of Kazakhstan via comparative qualitative research methods. As a result, an analysis of world experience shows that the notariate, which is a body of indisputable jurisdiction, is fully capable of taking on certain functions aimed at reducing conflict in at least civil and family relations. In conclusion, the bodies of inquiry and investigation are extremely reluctant to accept agreements on settlement of a legal dispute (conflict) already existing in the case through mediation